Reações multicomponentes na preparação de compostos nitrogenados polifuncionalizados - Wendler, Edison Perevalo (2010)
This PhD thesis covered was devoted to the preparation of nitrogenated intermediates by multicomponent reactions (3-MCR) with potential application in the bioactive compound synthesis. The developed methodology consisted on the coupling reaction of an organometallic compound, formed by an alkyne and a metal salt or complex, and a nitrogenated electrophile like as imines or iminium salts. In the first part of this work we reported the A3 coupling reaction of aldehydes, 4-piperidone hydrochloride monohydrate and alkynols giving the corresponding hydroxy alkynyl piperidin-4-ones, which are important synthetic building blocks. In the second part of the work was developed a coupling reaction using benzylamine as primary amine source in order to prepare amino alkynols with the benzil group. These compounds were employed, as synthetic intermediates, in the synthesis of bioactive five, six and seven membered alkaloids.